Proposed synchronization circuits connecting wind driven DFIG to the public grid - Mohamed Hussein Agamy; Fathe M. Allythi; Adel S. Nada (Institute of Advanced Engineering and Science, 2021)
This paper presents a tested proposal scheme to connect a DFIG driven by a wind turbine to the public grid. This scheme was implemented to drive an automatic transfer switch (ATS). Control of the phase sequence, phase difference, and the frequency of the injected power are achieved using these proposed control circuits. These circuits are practically implemented and laboratory tested. The system allows monitoring the rated frequency, synchronization, and fundamental magnitude. Simulation software such as Multi Sim and Proteus are used for system validation and compatibility. The implemented circuits are used for re-scaling the grid voltage to the logic level for real time comparison and calculations. In addition to the feature of data monitoring, the system can also log these data for the system debugging purposes. The system can be considered as a real time control where the measurements and the correction are made in few milliseconds (fractions of the fundamental cycle). The lower cost control circuits are implemented using an Arduino kit in addition to a discrete digital component. The simulation and experimental results are in satisfactory agreement showing the most salient features of this system.